Draft Eighth Five Year Plan 1990-95 Volume : VII Hill Areas Government of Assam - Planning Commission (Planning Commission, 1990)
The soil of both the Hill districts are laterite and varies. from clay to clay loan and are rich, in humus content. The two hill districts are primarily characterised with high to low hill slopes and valley area having quite a high potentialities for cultivation of a number of field crops. Considering its agro- climatic factors more thrust has been given for increasing, the yield per unit of areas in cases of Agril. crops by increasing crop, intensity of various crops in the basic aim. Further, for permanent horticultural crops, there is immense potentialities in these districts.
Government of Assam, Development Commissioner for the Hill Areas